2022
DOI: 10.3389/fpsyg.2022.859145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Satisfaction and Acceptability of an Online Parent Coaching Intervention: A Mixed-Methods Approach

Abstract: BackgroundParent-mediated intervention (PMI) has been studied in promoting skill acquisition or behavior change in the children with autism spectrum disorder. Most studies emphasize on the improvement of child’s core symptoms or maladaptive behaviors, making parental perceived competence and self-efficacy secondary. Yet, the evaluations of intervention implementation are under-reported, especially when translating such interventions into a new population or context. This research investigated the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…During the randomization process, three studies were deemed high-risk due to the absence of randomization [ 32 , 37 , 36 ]. In terms of outcome measurement, three studies were considered high-risk: one due to parental completion of assessments [ 35 ], and the other for the use of self-made scale [ 34 ] and reliance on a single scale throughout the research [ 23 ]. The remaining studies were categorized as low risk or presented some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…During the randomization process, three studies were deemed high-risk due to the absence of randomization [ 32 , 37 , 36 ]. In terms of outcome measurement, three studies were considered high-risk: one due to parental completion of assessments [ 35 ], and the other for the use of self-made scale [ 34 ] and reliance on a single scale throughout the research [ 23 ]. The remaining studies were categorized as low risk or presented some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggested that the use of tele-intervention in that procedure was effective in achieving goals. A subsequent study published by Qu et al [ 45 ] in a population with Autism Spectrum Disorder (ASD) used the same intervention method and obtained positive results in terms of family perception variables.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research continues this line of prevention and intervention in determining aspects of the health of infants aged 0 to 6 years, showing rates of effectiveness and acceptability, in which the figure of the family and its context are highlighted in the process [ 42 , 45 , 51 , 53 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to collect data on different dimensions of social validity, including goals, procedures, and outcomes, and across different times (e.g., before and after the intervention) when assessing social validity. Moreover, it is helpful to use the social validity data to understand other types of data and make adaptations to the intervention iteratively [37,38].…”
Section: Implications and Limitationsmentioning
confidence: 99%